Evolution and Stagnation of Image Guidance for Surgery in the Lateral Skull: A Systematic Review 1989–2020 - Daniel Schneider; Jan Hermann; Fabian Mueller; Gabriela O'Toole Bom Braga; Lukas Anschuetz; Marco Caversaccio; Lutz Nolte; Stefan Weber; Thomas Klenzner (Frontiers in Surgery, 2021)
Objective: Despite three decades of pre-clinical and clinical research into image guidance solutions as a more accurate and less invasive alternative for instrument and anatomy localization, translation into routine clinical practice for surgery in the lateral skull has not yet happened. The aim of this review is to identify challenges that need to be solved in order to provide image guidance solutions that are safe and beneficial for use during lateral skull surgery and to synthesize factors that facilitate the development of such solutions.Methods: Literature search was conducted via PubMed using terms relating to image guidance and the lateral skull. Data extraction included the following variables: image guidance error, imaging resolution, image guidance system, tracking technology, registration method, study endpoints, clinical target application, and publication year. A subsequent search of FDA 510(k) database for identified image guidance systems and extraction of the year of approval, intended use, and indications for use was performed. The study objectives and endpoints were subdivided in three time phases and summarized. Furthermore, it was analyzed which factors correlated with the image guidance error. Factor values for which an error ≤0.5 mm (μerror + 3σerror) was measured in more than one study were identified and inspected for time trends.Results: A descriptive statistics-based summary of study objectives and findings separated in three time intervals is provided. The literature provides qualitative and quantitative evidence that image guidance systems must provide an accuracy ≤0.5 mm (μerror + 3σerror) for their safe and beneficial application during surgery in the lateral skull. Spatial tracking accuracy and precision and medical image resolution both correlate with the image guidance accuracy, and all of them improved over the years. Tracking technology with accuracy ≤0.05 mm, computed tomography imaging with slice thickness ≤0.2 mm, and registration based on bone-anchored titanium fiducials are components that provide a sufficient setting for the development of sufficiently accurate image guidance.Conclusion: Image guidance systems must reliably provide an accuracy ≤0.5 mm (μerror + 3σerror) for their safe and beneficial use during surgery in the lateral skull. Advances in tracking and imaging technology contribute to the improvement of accuracy, eventually enabling the development and wide-scale adoption of image guidance solutions that can be used safely and beneficially during lateral skull surgery.